The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/cico.12321
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Landlords: Unintended Consequences for Poor Tenants

Abstract: This paper explores "hidden" ways by which cities may inadvertently undermine access to decent, stable, affordable housing-especially for vulnerable renter households-through regulations that sanction landlords for tenant activities on their property. In-depth semistructured interviews and ethnographic observations with 57 small-and medium-sized landlords in Cleveland, followed over 28 months, show that perceptions of risk, flowing specifically from "nuisance" and water regulations that rendered landlords acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 20 publications
(25 reference statements)
1
45
0
Order By: Relevance
“…With a limited supply of public and nonprofit housing, policy solutions seeking a broad impact must inevitably target private landlords, who serve as gatekeepers for the overwhelming majority of US renters. This focus aligns with research indicating that private landlords' decisions to set rent and screening criteria, accept or reject housing vouchers, and evict and select tenants significantly shape renters' housing experiences (Rosen 2014;Desmond 2016;Greif 2018;A. Travis 2019).…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations
“…With a limited supply of public and nonprofit housing, policy solutions seeking a broad impact must inevitably target private landlords, who serve as gatekeepers for the overwhelming majority of US renters. This focus aligns with research indicating that private landlords' decisions to set rent and screening criteria, accept or reject housing vouchers, and evict and select tenants significantly shape renters' housing experiences (Rosen 2014;Desmond 2016;Greif 2018;A. Travis 2019).…”
Section: Introductionsupporting
confidence: 70%
“…Adam Travis (2019) found that legal changes that decreased owners' financial risk prompted some rental owners to let their properties fall into disrepair, a cost borne by tenants, particularly those in poor neighborhoods. Meredith Greif (2018) likewise observed that landlords' business practices are sensitive to the legal environment. Rental owners in Cleveland feared water and nuisance regulations would increase their financial risk and responded with a host of tactics designed to offset that concern, including strict screening practices, higher rents, and informal surveillance and threats.…”
Section: The Limits Of Antidiscrimination Lawmentioning
confidence: 99%
See 2 more Smart Citations
“…The consequences of eviction are significant for individuals, families, neighborhoods, and communities (Babajide, Blum, Maniates, & Scher, 2016;Clark, 2017). Evictions most clearly impact the residential displacement of renters, as facing an eviction can increase renters' likelihood of experiencing homelessness, limit access to affordable housing options, and restrict eligibility for housing assistance (Babajide et al, 2016;Crane & Warnes, 2000;Desmond, 2016;Greif, 2018;Lindblom, 1991;Rosenblatt & DeLuca, 2012). But the impact of evictions extends far beyond residential displacement, as evictions often have a domino effect on the lives of renters.…”
Section: Introductionmentioning
confidence: 99%